A DATABASE MODEL FOR INCREASING THE SUCCESS OF INTERIOR DESIGN IN OPEN PLAN OFFICES IN TERMS OF ACOUSTIC COMFORT - Karaaslan, Tuğba; Yazıcıoğlu, Deniz Ayşe (Advances in Social Sciences Research Journal, 2015)
The relation between office interior design and employee performance has been an important area of research since many years. Many institutions have been trying new designs and techniques in new buildings within the purview of the studies done in this regard with an eye to increase the efficiency of their employees as well as retaining their employees by attracting them. To this end, the purview and purpose of this study have been determined as proposal of a database model for increasing the success of interior design in open plan offices in terms of acoustic comfort. Whom and how the data base model will be utilized as the study’s methodology has been described at the first stage. Subsequently, classification systematic of the database model has been created. The database model has been fictionalized in a holistic way basing on this classification systematic at the final stage. It is ensured to have access to design rules created as a result of various scientific studies as to increase interior design success in open-plan offices in terms of acoustic comfort by virtue of the proposed database model proposed within the purview of the study. Furthermore, it will be also enabled to reach information needed in application of design rules in the database and as to the products or materials sold in the sector. In other words, it will be possible to see which design rule will be able to be realized by which material or product and company information as to them will be made available. In addition, numerous different statistical results such as graphic of registration on the basis of design rule classes, number of design rules on the basis of products, will be able to be obtained thanks to the proposed database model. Such results will be able to be employed for different purposes in both academic and sectoral levels.